فاعلية برنامج تأهيلي قائم على المساندة الوالدية في تحسين مستوى التعلم المنظم ذاتيا لدى التلاميذ ذوي اضطراب قصور الانتباه وفرط الحركة - محمودي, خديجة (University of Eloued جامعة الوادي, 2021)
الملخص: يهدف البحث الحالي إلى التعرف على فاعلية برنامج تأهيلي قائم على المساندة الوالدية في مدى تحسين مستوى التعلم المنظم ذاتيا لدى تلميذ متمدرس بالسنة الأولى من التعليم المتوسط يعاني من اضطراب قصور الانتباه وفرط الحركة، وقد تم الاعتماد على برنامج تدريبي ينمي مهارة المراقبة الذاتية بما تتضمنه من التسجيل الذاتي أيضا، بغية تحقيق التنظيم الذاتي للتعلم وتعميمه أثناء تعلمه في المدرسة وبالتالي تحسين الأداء الدراسي والوصول إلى التفوق الأكاديمي، ومن أجل تحقيق هاته الأهداف انطلق البحث من التساؤل: - هل توجد فروق بين متوسطي درجات القياسين القبلي والبعدي على مقياس التعلم المنظم ذاتيا بعد تنفيذ البرنامج التأهيلي القائم على المساندة الوالدية لدى التلميذ ذي اضطراب قصور الانتباه وفرط الحركة؟ اعتمد البحث على المنهج شبه التجريبي المصمم على الفرد الواحد الذي يعاني من اضطراب قصور الانتباه وفرط الحركة، وتم التأكد من ذلك باستخدام مقياس لتشخيص اضطراب(ADHD) إضافة إلى ملخص دراسة الحالة بما تحتويه من فحوصات نفسية وطبية، وطُبّق عليه البرنامج التأهيلي من طرف الوالدين مع القياس القبلي والبعدي بالاستعانة بمقياس "بوردي" للتعلم المنظم ذاتيا الذي يشتمل على أربعة أبعاد وهي: وضع الهدف والتخطيط، مراقبة الذات والاحتفاظ بالسجلات، التسميع والحفظ، طلب المساعدة الاجتماعية. وبعد التحليل الإحصائي لنمط التصميم شبه التجريبي للفرد الواحد الذي يعتمد أساسا على الفروق بين المتوسطات الحسابية؛ تم التوصل إلى أن البرنامج التأهيلي القائم على المساندة الوالدية ذو فاعلية في تحسين مستوى التعلم المنظم ذاتيا لدى التلميذ الذي يعاني من اضطراب قصور الانتباه وفرط الحركة، وبناء على نتائج الدراسة فقد قُدمت مجموعة من المقترحات. abstract: The current research aims to identify the effectiveness of a rehabilitation program based on parental support in improving the level of self-organized learning for a student in the first year of intermediate education who suffers from attention deficit hyperactivity disorder. A training program has been relied on to develop the self-monitoring skill, including the registration it includes. Self-regulation also, in order to achieve self-regulation of learning and its generalization during learning in school and thus improve academic performance and reach academic excellence. In order to achieve these goals, the research started from the following question: - Are there statistically significant differences between the mean scores of the pre and post measurements on the self-organized learning scale after implementing the rehabilitation program based on parental support for the student with attention deficit hyperactivity disorder? The research relied on the quasi-experimental approach designed on the individual who suffers from attention deficit hyperactivity disorder, and this was confirmed using a scale for diagnosing ADHD in addition to a summary of the case study with its psychological and medical examinations, and the rehabilitation program was applied by the parents With the pre- and post-measurement using the Purdy scale of self-organized learning, which includes four dimensions: goal setting and planning, self-monitoring and record-keeping, recitation and memorization, and seeking social assistance. After the statistical analysis of the quasi-experimental design pattern for one individual, it was concluded that the rehabilitation program based on parental support is effective in improving the level of self-organized learning for the student who suffers from attention deficit hyperactivity disorder, and based on the results of the study, a set of recommendations were presented
مذكرة ماستر في علوم التربية تخصص تربية خاصة
Keywords: البرامج التأهيلية، المساندة الوالدية، التعلم المنظم ذاتيا، قصور الانتباه، فرط الحركة; Programmes de réadaptation, soutien parental, apprentissage autorégulé, déficit d'attention, hyperactivité; Rehabilitation programs, parental support, self-regulated learning, attention deficit, hyperactivity